Precision pharmacology in menopause: advances, challenges, and future innovations for personalized management - Guo, Zhi-qing (Frontiers in Reproductive Health, 2025)
Menopause, characterized by ovarian function cessation and estrogen decline, affects over a billion women globally, leading to vasomotor symptoms (VMS), genitourinary syndrome of menopause (GSM), mood disturbances, osteoporosis, and cardiovascular risks. Pharmacological management is essential for symptom alleviation and long-term health, yet debates on hormone therapy risks necessitate personalized approaches. This review synthesizes recent advances in menopause pharmacology, evaluating hormonal therapies, non-hormonal alternatives, emerging options, challenges, and future directions. A systematic literature search, following PRISMA guidelines, was conducted via PubMed, Cochrane Library, and Web of Science (2015–2025) using keywords like “menopause pharmacological therapy,” “hormone replacement risks,” “non-hormonal VMS treatments,” and “ovarian aging modulators.” Two independent reviewers screened abstracts and full texts, including RCTs, meta-analyses, and expert consensuses focused on efficacy, safety, pharmacokinetics, and mechanisms; exclusions applied to non-English or pre-2015 studies. Hormonal therapies (MHT/HRT), evolved from WHI trials, effectively reduce VMS by 70%–90% and preserve bone density via estrogen receptor modulation, with low-dose transdermal regimens minimizing VTE and breast cancer risks per NAMS/IMS guidelines. Non-hormonal options like SSRIs/SNRIs (40%–60% efficacy) and NK3R antagonists (fezolinetant, 50%–65% VMS reduction) suit contraindicated patients. Emerging therapies, including phytoestrogens, testosterone for libido, and ovarian aging modulators (e.g., AMH analogs), address unmet needs. Special populations (e.g., POI, cancer survivors) require tailored strategies, while challenges include access inequities and long-term data gaps. Advancements underscore precision pharmacology's shift to individualized, non-hormonal treatments. Future priorities: biomarker-guided personalization, AI-driven discovery, and novel delivery systems to enhance efficacy, reduce risks, and improve QoL for menopausal women.